Development Of A Web-Based Supply Chain Management System At The Minahasa Cooperatives And Umkm Service Using The K-Means Algorithm - Jessica Daniel Joni; Quido C Kainde (Jurnal Minfo Polgan, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) plays a very important role in the regional economy. Therefore, a Supply Chain Management (SCM) system is a very important aspect of business operations that involves coordinating the activities involved in the production and delivery of goods and services to customers. SCM can be applied to small and medium enterprises (MSMEs) in the Minahasa Cooperatives and UMKM Department to improve their performance and competitiveness. SCM aims to efficiently manage the flow of goods, information and capital from suppliers to end consumers. This research aims to design and develop a web-based Supply Chain Management system for the Department of Cooperatives and MSMEs by applying the k-means algorithm for customer segmentation. In this research, the K-Means algorithm is used to group similar data points. This algorithm works by defining clusters so that the total intra-cluster variation (known as total within-cluster variation) is minimized. The results of this research can help increase the efficiency and effectiveness of supply chain management. In developing this system, customer, supplier and product data were successfully grouped into several groups based on similar characteristics using the k-means algorithm. Apart from that, the system that has been developed can also help facilitate the SCM process by utilizing information technology.